The large GTPase atlastin controls ER remodeling around a pathogen vacuole. Issue 2 (4th March 2018) - Steiner, Bernhard; Weber, Stephen; Kaech, Andres; Ziegler, Urs; Hilbi, Hubert
ABSTRACT: The ubiquitous environmental bacterium Legionella pneumophila is the causative agent of Legionnaires' pneumonia and replicates in free-living protozoa and mammalian macrophages in a specific compartment, the Legionella -containing vacuole (LCV). LCVs communicate with the endosomal, retrograde and secretory vesicle trafficking pathway, and eventually tightly interact with the endoplasmic reticulum (ER). In Dictyostelium discoideum amoebae and macrophages, the ER tubule-resident large GTPase Sey1/atlastin3 (Atl3) accumulates on LCVs and promotes LCV expansion and intracellular replication of L. pneumophila . Fluorescence microscopy of D. discoideum infected with L. pneumophila indicated that Sey1 is involved in extensive ER remodeling around LCVs. An ultrastructural analysis confirmed these findings. Moreover, dominant negative Sey1_K154A compromises ER accumulation on LCVs and causes an aberrant ER morphology in uninfected D. discoideum as well as in amoebae infected with avirulent L. pneumophila that lack a functional type IV secretion system. Thus, the large, dynamin-like GTPase Sey1/Atl3 controls circumferential ER remodeling during LCV maturation.